The T-type calcium channel antagonist Z944 disrupts prepulse inhibition in both epileptic and non-epileptic rats. (22nd September 2016) - Marks, Wendie N.; Greba, Quentin; Cain, Stuart M.; Snutch, Terrance P.; Howland, John G.
Highlights: The effects of Z944 on PPI in epileptic and non-epileptic rat strains was tested. Z944 significantly impaired PPI in Wistar rats and GAERS. Z944 dose-dependently affected startle in the Wistar strain only. T-type calcium channel activity contributes to PPI. Abstract: The role of T-type calcium channels in brain diseases such as absence epilepsy and neuropathic pain has been studied extensively. However, less is known regarding the involvement of T-type channels in cognition and behavior. Prepulse inhibition (PPI) is a measure of sensorimotor gating which is a basic process whereby the brain filters incoming stimuli to enable appropriate responding in sensory rich environments. The regulation of PPI involves a network of limbic, cortical, striatal, pallidal and pontine brain areas, many of which show high levels of T-type calcium channel expression. Therefore, we tested the effects of blocking T-type calcium channels on PPI with the potent and selective T-type antagonist Z944 (0.3, 1, 3, 10 mg/kg; i.p.) in adult Wistar rats and two related strains, the Genetic Absence Epilepsy Rats from Strasbourg (GAERS) and Non-Epileptic Control (NEC). PPI was tested using a protocol that varied prepulse intensity (3, 6, and 12 dB above background) and prepulse-pulse interval (30, 50, 80, 140 ms). Z944 decreased startle in the Wistar strain at the highest dose relative to lower doses. Z944 dose-dependently disrupted PPI in the Wistar and GAERS strains with the most potent effect observed with the higher doses. These findings suggest that T-type calcium channels contribute to normal patterns of brain activity that regulate PPI. Given that PPI is disrupted in psychiatric disorders, future experiments that test the specific brain regions involved in the regulation of PPI by T-type calcium channels may help inform therapeutic development for those suffering from sensorimotor gating impairments.